2018
DOI: 10.1111/psyg.12355
|View full text |Cite
|
Sign up to set email alerts
|

Physical abuse of the elderly: a 4‐year retrospective evaluation in the emergency department

Abstract: There may be three conclusions for the current study: First, although EPA is a rare problem for patients referred to emergency services, health professionals should be suspicious when examining patients 65 years or older because of the difficulties of diagnosing EPA. Second, in patients with no history of suspicious trauma or suspicious radiological imaging results, EPA is also common. Third, because of the undetected EPA mechanism, patients should be examined forensically in suspicious cases and deaths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
(38 reference statements)
0
6
0
1
Order By: Relevance
“…Additionally, 69.9% of all cases, 62.1% of VPA and 84.9% of VSV were male. Some studies on the gender distribution of elder abuse victims reported that men are exposed to more violence, while others indicated that women are exposed to more violence (Altintop & Tatli, 2019;de Sousa et al, 2016;Karbeyaz & Çelikel, 2017;Kılıç Öztürk et al, 2017;Rodrigues et al, 2019;Rosen et al, 2016).…”
Section: Overall Study Sample Characteristicsmentioning
confidence: 99%
“…Additionally, 69.9% of all cases, 62.1% of VPA and 84.9% of VSV were male. Some studies on the gender distribution of elder abuse victims reported that men are exposed to more violence, while others indicated that women are exposed to more violence (Altintop & Tatli, 2019;de Sousa et al, 2016;Karbeyaz & Çelikel, 2017;Kılıç Öztürk et al, 2017;Rodrigues et al, 2019;Rosen et al, 2016).…”
Section: Overall Study Sample Characteristicsmentioning
confidence: 99%
“…Lo más habitual había sido la agresión directa (63%). Los autores consideran que estas cifras representan una proporción muy baja en relación con la realidad por los recelos del anciano para denunciarlo e incluso para acudir a un hospital en busca de ayuda (33).…”
Section: -Abusos Y Malos Tratos Económicos Y Financieros Abusos Y Munclassified
“…Community health nurse has to make visits in houses and old age homes for the same. The main aspects included must be regular physical activity, diet, weak bones, oral care, and prevention of accidents, sight, hearing, all health problems and common ailments like incontinence, constipation etc [11][12][13].…”
Section: Introductionmentioning
confidence: 99%